PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN TRANSPORTASI ONLINE GRAB DI JAKARTA UTARA - Florentina Claresta; Tony Sitinjak (Jurnal Ilmiah Hospitality, 2022)
Transportation is a very basic need that is needed by everyone to carry out activities. Along with the times, various online transportations have started to appear that make it easier for everyone to move. However, often the quality of services provided by the company does not satisfy customers, and the brand image that is built is also less attached to the minds of consumers. The theory used to support this research is the definition of service quality, brand image, and customer satisfaction proposed by Philip Kotler and Kevin Lane Keller; Gary Armstrong and Philip Kotler; Tjiptono; Zeithmal, Bitner, dan Gremler; and Sugiharti. The object of this research is service quality on customer satisfaction and brand image on Grab online transportation customer satisfaction The method in this study uses a causal method by using a questionnaire to collect data. To determine the sample, the method used is non-probability sampling with judgment sampling technique. The results of the analysis show that service quality and Grab's online transportation brand image also have a significant and positive influence on customer satisfaction. The conclusion of this study is that the service quality variable and the Grab online transportation brand image variable have a significant influence on customer satisfaction.